2009
DOI: 10.1007/s11262-009-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new variants of SCMV causing sugarcane mosaic in India and assessing their genetic diversity in relation to SCMV type strains

Abstract: Sugarcane mosaic virus (SCMV) is one of the two causative viruses of mosaic in sugarcane, a sugar crop widely grown under tropical and subtropical conditions worldwide. Although molecular characterization of SCMV strains was reported from many countries, strains occurring in India, a major sugarcane producer have not been reported so far. Twenty-six sugarcane samples represented by seven major sugarcane growing states in India and USA were subjected to reverse-transcription polymerase chain reaction (RT-PCR) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…This might be in part explained by the fact that the tubers from the same origin are disseminated for multiplication of orchid production, leading to the high degree of observed CP conservation. In contrast to ORSV, some studies showed geographic variation of a few plant viruses, based on the determination of only CP sequences of virus isolates and various analyses of the determined sequences [22][23][24][25][26][27]. These studies support that the validity of our analysis of CP gene sequences is sufficient for investigating geographic variation of ORSV isolates.…”
Section: Discussionsupporting
confidence: 68%
“…This might be in part explained by the fact that the tubers from the same origin are disseminated for multiplication of orchid production, leading to the high degree of observed CP conservation. In contrast to ORSV, some studies showed geographic variation of a few plant viruses, based on the determination of only CP sequences of virus isolates and various analyses of the determined sequences [22][23][24][25][26][27]. These studies support that the validity of our analysis of CP gene sequences is sufficient for investigating geographic variation of ORSV isolates.…”
Section: Discussionsupporting
confidence: 68%
“…To confirm the SCSMV infection and to rule out other prevalent and co-existing diseases (Prabu et al 2008), the collected plant samples were tested for SCSMV, sugarcane mosaic virus (SCMV), and sugarcane grassy shoot phytoplasma (SCGS) infection by RT-PCR and PCR using the reported specific primers (Viswanathan et al 2009;Xu et al 2010). Presence of SCSMV infection in the plant materials used in this study has been confirmed (data not shown).…”
mentioning
confidence: 60%
“…It appears that virus mixtures are more virulent than single infections (Xu et al 2008). In addition, new strains or genomic variants of SCMV continue to be reported in different countries (Perera et al 2009;Viswanathan et al 2009;Gao et al 2011;Padhi and Ramu 2011). These outbreaks indicate that even though SCMV has been long known, it remains an agricultural threat (Wu et al 2012).…”
Section: Introductionmentioning
confidence: 99%